Pengembangan Pola Pendidikan Ekonomi Informal Dalam Penguatan Literasi Ekonomi Dan Kewirausahaan Pada Pelaku UMKM Di Kota Selong (Di Kelurahan Denggen) - Muhamad Juaini; Muhammad Rapii; Tiara Puspa Sari; Ummi Qorib Absoh; Maya Andini (JPEK: Jurnal Pendidikan Ekonomi dan Kewirausahaan, 2025)
Economic education within the family environment is part of informal education that occurs in an unprogrammed manner, but through a process of habituation and role modeling. This study aims to examine and analyze the characteristics of informal economic education that occurs within households, thereby forming patterns of informal economic education as an effort to shape good economic behavior. The data in this study were analyzed using qualitative analysis through the processes of data collection, data reduction, data presentation, and verification. The results showed that learning occurs not only through formal channels, but also organically through direct experience, social interaction, informal mentoring, observation, and the use of digital and community resources. These patterns are adaptive, contextual, and driven by the practical needs of MSMEs to survive and thrive. Significantly, this informal education has proven to be a major catalyst in strengthening functional economic literacy, where MSMEs gradually develop an understanding and ability to manage the financial aspects of their businesses, such as costing, pricing, cash flow management, and risk mitigation